Geoeconomic Policies for Regional Development: Turkey as a Catalyst for Eastern Europe - Inan, Sukru (Ekonomika, 2005)
This paper examines the influence of geoeconomic policies on development. The new age is characterized by not political or ideological rivalry but by economic competition. States do not aim at conquering lands but rather at dominating and controlling markets. That process brings the discussion that the age is whether a geoeconomic age or a neo-mercantilist age with the writings of pundit writers of geoeconomics in terms of the economic policies of developed and developing countries. In the geoeconomic world developed countries mainly apply neo-mercantilist policies towards the developing countries, and as a response developing countries that were “second orders” or “middle powers” of the geopolitical era generate their own regional geo-mercantilist policies and closer economic relations with neighbor countries. Turkey’s strategic and geopolitical importance is continuing with its geoeconomic importance in the new era. Since the 1980s Turkey’s growth and industryoriented policies have shifted from the realm of public policy to a market-driven domain. And later, with the collapse of the USSR and the end of the Cold War, the “Iron Curtain” around Turkey has absented. These two transformations gave Turkey a great chance with her historical, cultural and economic ties to form a geoeconomic space and to become an engine of regional development. This study investigates the importance of Turkey for regional development with its geoeconomic policies in terms of energy. trade, and investment policies. Turkey as a bridge or a frontier between East and West could play an effective role. For Eastern Europe, Turkey will create a catalyst effect as a bridge, however, its effect will be an impediment as a frontier.